Optical fibre sensors for respiration monitoring in sports and healthcare - Limweshasin, Nat (2024)
The ultimate objective of this PhD thesis is the development of fibre optic sensor systems for respiratory rate and volume monitoring with the aim of contributing to the improvement of patients and athlete safety, recovery, and performance. Particularly, wearable devices which facilitate prolonged, continuous respiration measurements through user comfort as well as portability were implemented.